The American Experience in Bioethics - Newton, Lisa. author. aut Link
VIII, 81 p.
Keywords: This volume tracks the development in the United States of the field of Bioethics, Ethics applied to the disciplines of medicine, nursing, and health care in general, including medical research and the complex economic and political problems surrounding the provision of medical and nursing care. It explains how the United States developed, case by case, the central rules and principles of ER ethics in the Health Care System. The discussion includes the controversies centering on birth, death, clinical research, experimental procedures (cloning, reproductive technology, organ transplants), and ends with a substantial suggestion on the provision of health care for all.